2002
DOI: 10.1099/00221287-148-4-961
|View full text |Cite
|
Sign up to set email alerts
|

Physiological consequences associated with overproduction of Mycobacterium tuberculosis FtsZ in mycobacterial hosts

Abstract: The ftsZ gene of Mycobacterium tuberculosis H37Rv has been characterized as the first step in determining the molecular events involved in the cell division process in mycobacteria. Western analysis revealed that intracellular levels of FtsZ are growth phase dependent in both M. tuberculosis and Mycobacterium smegmatis. Unregulated expression of M. tuberculosis ftsZ from constitutive hsp60 and dnaA promoters in M. tuberculosis hosts resulted in lethality whereas expression from only the hsp60 promoter was toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 43 publications
(38 reference statements)
6
84
0
Order By: Relevance
“…To gain insights into the cell division process in mycobacteria, we began characterizing M. tuberculosis ftsZ (ftsZ tb ) expressed from heterologous promoters. We showed that in M. tuberculosis, expression of ftsZ tb from the ami promoter (amip) in a replicating vector did not result in a consistent level of expression whereas that from the Mycobacterium avium dnaA promoter led to non-viability (Dziadek et al, 2002). In contrast, viable M. smegmatis transformants producing consistent levels of FtsZ tb were obtained with both plasmids.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…To gain insights into the cell division process in mycobacteria, we began characterizing M. tuberculosis ftsZ (ftsZ tb ) expressed from heterologous promoters. We showed that in M. tuberculosis, expression of ftsZ tb from the ami promoter (amip) in a replicating vector did not result in a consistent level of expression whereas that from the Mycobacterium avium dnaA promoter led to non-viability (Dziadek et al, 2002). In contrast, viable M. smegmatis transformants producing consistent levels of FtsZ tb were obtained with both plasmids.…”
Section: Introductionmentioning
confidence: 84%
“…Mycobacterium smegmatis. The cell division process in M. smegmatis is also not well understood (Dziadek et al, 2002;Gomez & Bishai, 2000). Although the project to determine the nucleotide sequence of M. smegmatis is not complete, its genome appears to contain homologues of all annotated M. tuberculosis cell division genes [see http:// www.tigr.org/tdb/mdb/mdbinprogress.html (Dziadek et al, 2002)].…”
Section: Introductionmentioning
confidence: 99%
“…When calculated, ϳ12,000 MtrB molecules/ M. tuberculosis cell were found. Slightly lower levels (ϳ7500 molecules) of MtrB were found in M. smegmatis, which grows more rapidly, with an average doubling time of 3 h. We reported earlier that the intracellular levels of FtsZ, MtrA, and CrgA proteins in M. tuberculosis correspond to 30,000, 4,000, and 20,000 molecules/actively growing cell, respectively (8,20,21). Thus, MtrB appears to be a relatively abundant protein in M. tuberculosis.…”
Section: Mtrb Is An Abundant Protein That Localizes To Cell Polesmentioning
confidence: 99%
“…Preparation of cellular lysates of M. tuberculosis by bead-beating and Western blotting protocols were as described (Dziadek et al, 2002). Known amounts of cellular lysates based on the equivalent protein concentration were resolved by SDS-PAGE, transferred to Protran nitrocellulose membranes (Schleicher and Schuell).…”
Section: Preparation Of Cellular Lysates and Western Blottingmentioning
confidence: 99%